Middle-Preserving Pancreatectomy: An Interesting Procedure for Pancreas-Sparing Resection - Sperti, Cosimo; Polizzi, Maria Laura; Moro, Margherita; Beltrame, Valentina; Pedrazzoli, Sergio (JOP. Journal of the Pancreas, 2010)
Context Total pancreatectomy is the treatment of choice for multicentric diseases involving the head and the body-tail of the pancreas. Middle-preserving pancreatectomy is a recently reported alternative procedure when the pancreatic body is spared from disease. We report on the successful preservation of the pancreatic body in a patient harboring a multicentric intraductal papillary mucinous neoplasia (IPMN). Case report A multicentric IPMN was diagnosed in a 59-year-old man. A standard pylorus preserving pancreaticoduodenectomy was performed, followed by a spleen-preserving distal pancreatectomy. The splenic vessels were carefully preserved. The residual 5 cm of the pancreatic body were anastomosed to the jejunum after verifying that the resection line on both sides was negative at frozen section examination. The postoperative course was complicated by transient peritoneal bleeding managed with angiographic embolization of the splenic artery. A borderline mixed type IPMN of the head and chronic pancreatitis of the tail were found at pathological examination. Eleven months after surgery, the patient is well and disease free; glycemic control is achieved by diet. Conclusion A middle-preserving pancreatectomy can be performed safely for multicentric IPMNs involving the head and the body-tail of the gland. It can prevent problems with the glycemic control that usually follows total pancreatectomy. Image: The end result of middle-preserving pancreatectomy with double jejunal loop reconstruction.